The cost of travel: How dispersal ability limits local adaptation in host–parasite interactions. (29th December 2020) - Johnson, Pieter; Calhoun, Dana M.; Moss, Wynne E.; McDevitt‐Galles, Travis; Riepe, Tawni B.; Hallas, Joshua M.; Parchman, Thomas L.; Feldman, Chris R.; Achatz, Tyler J.; Tkach, Vasyl V.; Cropanzano, Josh; Bowerman, Jay; et al.
Abstract: Classical theory suggests that parasites will exhibit higher fitness in sympatric relative to allopatric host populations (local adaptation). However, evidence for local adaptation in natural host–parasite systems is often equivocal, emphasizing the need for infection experiments conducted over realistic geographic scales and comparisons among species with varied life history traits. Here, we used infection experiments to test how two trematode (flatworm) species ( Paralechriorchis syntomentera and Ribeiroia ondatrae ) with differing dispersal abilities varied in the strength of local adaptation to their amphibian hosts. Both parasites have complex life cycles involving sequential transmission among aquatic snails, larval amphibians and vertebrate definitive hosts that control dispersal across the landscape. By experimentally pairing 26 host‐by‐parasite population infection combinations from across the western USA with analyses of host and parasite spatial genetic structure, we found that increasing geographic distance—and corresponding increases in host population genetic distance—reduced infection success for P .  syntomentera, which is dispersed by snake definitive hosts. For the avian‐dispersed R. ondatrae, in contrast, the geographic distance between the parasite and host populations had no influence on infection success. Differences in local adaptation corresponded to parasite genetic structure; although populations of P .  syntomentera exhibited ~10% mtDNA sequence divergence, those of R. ondatrae were nearly identical (<0.5%), even across a 900 km range. Taken together, these results offer empirical evidence that high levels of dispersal can limit opportunities for parasites to adapt to local host populations. Abstract : By experimentally crossing host and parasite source populations, this study tests how trematode parasite infection success depends on both the geographic proximity of amphibian hosts as well as the parasite's dispersal ability (bird‐ vs. snake‐dispersed). See Fig. 2 for more details.